Bone marrow transplant recipients and their compliance with sun‐protection measures in Queensland, Australia. Issue 4 (13th February 2020) - Biswas, Neela; Deen, Jacqueline; Teare, Holly; Robertson, Ivan
Abstract: There is no current published work on the sun‐protection practices of bone marrow transplant recipients. The burden of post‐transplant skin malignancy is a growing public health concern. This paper evaluates the compliance of bone marrow transplant recipients with advice about sun protection through a cross‐sectional observational study involving participants completing a questionnaire regarding sun protection. Whilst most bone marrow transplant patients recalled receiving education (94%) and understood why they required additional precautions (84%), half did not practice adequate photoprotection. Future research should explore barriers to non‐compliance with sun‐protection measures in bone marrow transplant patients so additional interventions can be more targeted within this population.